The Algerian revolution and its role in liberating the peoples of Africa - hadjersi, khadra; djouiba, abdelkamel (Journal of Social Sciences and Humanities, 2021)
The Algerian revolution, through its struggle goals and its human and peaceful content, put forward a holistic concept to eliminate the colonial system in all its forms. Therefore, it did not only announce the popular revolution against the French occupation on the land of Algeria, but declared it a revolution against colonialism in all its forms and types, a revolution against tyranny and exploitation, anywhere in the world The Algerian revolution, by announcing the armed struggle, sought to implement international law, which is the right of peoples to self-determination, international peace and security, and joint work with world countries in order to eliminate colonial imperialism in the third world countries, and under this framework the National Liberation Front was keen on strengthening the bonds of unity and cooperation. In the African liberation struggle, considering that the liberation of the African continent from foreign colonialism is an integral part of the struggle and struggle of the Algerian people, and I worked with various media, diplomatic and political means to involve the African peoples in the revolutionary liberation tide and to adopt the Algerian model in the liberation struggle to achieve the freedom and unity of the continent.